COVID-19 booster enhances IgG mediated viral neutralization by human milk in vitro - Valcarce, Vivian; Stafford, Lauren Stewart; Neu, Josef; Parker, Leslie; Vicuna, Valeria; Cross, Tyler; D'Agati, Olivia; Diakite, Sisse; Haley, Addison; Feigenbaum, Jake; Al Mahmoud, Mahmoud Y.; Visvalingam, Anjali; et al. (Frontiers in Nutrition, 2024)
Background Facilitated by the inability to vaccinate, and an immature immune system, COVID-19 remains a leading cause of death among children. Vaccinated lactating mothers produce specific SARS-CoV-2 antibodies in their milk, capable of neutralizing the virus in vitro. Our objective for this study is to assess the effect of COVID-19 booster dose on SARS-CoV-2 antibody concentration and viral neutralization in milk, plasma, and infant stool. Methods Thirty-nine mothers and 25 infants were enrolled from December 2020 to May 2022. Milk, maternal plasma, and infants' stool were collected at various time-points up to 12 months following mRNA COVID-19 vaccination. A subgroup of 14 mothers received a booster dose. SARS-CoV-2 antibody levels and their neutralization capacities were assessed. Results Booster vaccination led to significantly higher IgG levels within human milk and breastfed infants' stool. In vitro neutralization of VSV-gfp-SARS-CoV-2-S-gp, a laboratory safe SARS-CoV-2 like pseudovirus, improved following the booster, with a 90% increase in plasma neutralization and a 60% increase in milk neutralization. We found that post-booster neutralization by human milk was highly correlated to SARS-CoV-2 IgG level. In support of our correlation result, Protein G column depletion of IgG in milk yielded a significant reduction in viral neutralization (p = 0.04). Discussion The substantial increase in neutralizing IgG levels in milk and breastfed infants' stool post-booster, coupled with the decrease in milk neutralization capabilities upon IgG depletion, underscores the efficacy of booster doses in augmenting the immune response against SARS-CoV-2 in human milk.